Therapeutic Potential of POU3F3, a Novel Long Non-coding RNA, Alleviates the Pathogenesis of Osteoarthritis by Regulating the miR-29a- 3p/FOXO3 Axis - Shi, Mingmin; Sun, Menghao; Wang, Cong; Shen, Yue; Wang, Yangxin; Yan, Shigui (Current Gene Therapy, 2022)
Background: Osteoarthritis (OA) is the predominant threat to the health of the elderly, and it is crucial to understand the molecular pathogenetic mechanisms involved in it. This study aims to investigate the role of a well-studied cancer-related long non-coding RNA (lncRNA)-POU3F3 in OA and its implicated molecular mechanisms. Methods: The expression of POU3F3 and miR-29a-3p was examined in osteoarthritis patients, as well as destabilization of the medial meniscus (DMM) mouse OA model and IL- 1β induced chondrocytes cell OA model, by quantitative real-time PCR. The interaction between POU3F3, miR-29a-3p and transcription factor forkhead box O3 (FOXO3) was verified via dual-luciferase reporter analysis and RNA immunoprecipitation analyses. Cell proliferation and apoptosis were evaluated by cell viability assay and flow cytometry, respectively. Cartilage extracellular matrix (ECM) degradation was investigated with ELISA and western blotting. In addition, the in vivo regulation of POU3F3 in OA was verified by intra-articular injection of lentivirus overexpression POU3F31 in mice models. Results: The expression level of POU3F3 was decreased in OA patients/animal cartilage tissues and IL-1β-stimulated in vitro chondrocyte model. POU3F3 overexpression inhibited IL-1β-induced injury of chondrocytes, enhancing cell viability, suppressing apoptosis and inflammatory cytokine secretion, rescuing metabolic dysfunction, and restraining autophagy in vitro. Mechanistically, Luciferase reporter and RNA immunoprecipitation (RIP) assays indicated that miR-29a-3p could directly bind to POU3F3, and FOXO3 was a target gene of miR-29a-3p. Functional rescue assays confirmed this POU3F3/miR-29a-3p/FOXO3 axis in chondrocytes during OA occurrence. Furthermore, intraarticularly delivery of lentivirus containing POU3F3 alleviates the damage in mouse OA model in vivo. Conclusion: In conclusion, this work highlights the role of the POU3F3/miR-29a-3p/FOXO3 axis in the OA pathogenesis, suggesting this axis as a potential therapeutic target for OA.
Keywords: FOXO3